2009
DOI: 10.1021/jp8113094
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of MnO2 Nanorods in Neutral Aqueous Electrolytes as a Cathode for Asymmetric Supercapacitors

Abstract: The electrochemical performance of MnO 2 nanorods prepared by a precipitation reaction was investigated in 0.5 mol/L Li 2 SO 4 , Na 2 SO 4 , and K 2 SO 4 aqueous electrolyte solutions. Results show that at the slow scan rates, the nanorods show the largest capacitance (201 F/g) in Li 2 SO 4 electrolyte since the reversible intercalation/ deintercalation of Li + in the solid phase produces an additional capacitance besides the capacitance based on the absorption/desorption reaction. At fast scan rates they show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
362
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 657 publications
(392 citation statements)
references
References 28 publications
13
362
0
2
Order By: Relevance
“…In contrast to the bare SWNT thin film electrode, the Nyquist plot of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode shows that the imaginary part of impedance increases sharply at lower frequency, which indicates that SWNT films retain their electron-transfer capability even with the integration of RuO 2 nanowires [39]. It can be seen that the diameters of the semicircle in the Nyquist plot of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode is smaller than that of the bare SWNT thin film electrode, which means that the electrochemical reactions on the electrode/electrolyte interface of hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode are more facile than on the bare SWNT thin film electrode [40]. In addition, the point intersecting with the real axis in the high frequency range (10 kHz) indicates that the ESR of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode (22 Ω) is lower than that of the bare SWNT thin film electrode (43 Ω), showing that the integration of RuO 2 nanowires with printed SWNT films increases the conductivity of the printed SWNT thin film electrode.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast to the bare SWNT thin film electrode, the Nyquist plot of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode shows that the imaginary part of impedance increases sharply at lower frequency, which indicates that SWNT films retain their electron-transfer capability even with the integration of RuO 2 nanowires [39]. It can be seen that the diameters of the semicircle in the Nyquist plot of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode is smaller than that of the bare SWNT thin film electrode, which means that the electrochemical reactions on the electrode/electrolyte interface of hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode are more facile than on the bare SWNT thin film electrode [40]. In addition, the point intersecting with the real axis in the high frequency range (10 kHz) indicates that the ESR of the hybrid RuO 2 nanowire/SWNT nanostructured thin film electrode (22 Ω) is lower than that of the bare SWNT thin film electrode (43 Ω), showing that the integration of RuO 2 nanowires with printed SWNT films increases the conductivity of the printed SWNT thin film electrode.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, pseudocapacitors are being developed to improve the energy density of devices since pseudocapacitors store and deliver energy through redox reactions, leading to high specific capacitance [11,12]. Transition metal oxides such as MnO 2 , NiO, Fe 2 O 3 and Co 3 O 4 are being studied as candidate materials for pseudocapacitor electrodes [11][12][13][14][15][16][17][18]. Although metal oxides alone offer high specific capacitance, they deliver low power density and poor rate capability (dramatic drop of specific capacitance with an increase at a high scan rate) due to poor electronic conductivity [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have done researches dealing with MnO 2 /carbon composites and have known that MnO 2 possesses several advantages on top of carbon material, such as high capacitance, low price, environmental compatibility and natural abundance in other applications, such as supercapacitor and Lithium-ion battery [13][14][15][16]. However, no previous MnO 2 /carbon composite materials as electrodes in CDI studies have been reported.…”
Section: Introductionmentioning
confidence: 99%